Preparation of a Novel Nanocomposite of Polyaniline Core Decorated with Anatase-TiO2 Nanoparticles in Ionic Liquid/Water Microemulsion. (22nd November 2011) - Guo, Yanni; He, Deliang; Xia, Sanbao; Xie, Xin; Gao, Xiang; Zhang, Quan
Abstract : Polyaniline core decorated with TiO2 (PANI-TiO2 ) nanocomposite particles was successfully synthesized in ionic liquid/water (IL/water) microemulsion in the presence of anatase TiO2 nanoparticles. The TiO2 nanoparticles had been dispersed beforehand in OP-10 and n -butanol to weaken the strong particles agglomeration of TiO2 . The PANI-TiO2 nanocomposites were characterized by fourier transform infrared spectroscopy (FTIR), ultraviolet visible spectroscopy (UV-Vis), scanning electron microscopy (SEM), and transmission electron microscope (TEM), and their electrochemical behavior was estimated by the electrochemical workstation. SEM micrographs showed that the nanocomposites exhibited spherical morphology with particle sizes about 70 nm. The TEM result showed that the PANI-TiO2 nanocomposites had a novel structure and that nanocrystalline TiO2 deposited onto the surface of PANI, which was different from the reported structure of TiO2 -PANI nanocomposites. Both FTIR and UV-Vis spectra indicate that polyaniline and nano-TiO2 particles are not simply blended or mixed up. A possible reaction mechanism for this nanocomposite preparation is suggested and analyzed.